Well-posedness for a class of frictional contact models via mixed variational formulations. (June 2019) - Chivu Cojocaru, Mariana; Matei, Andaluzia
Abstract: We analyze a class of frictional contact problems by means of a Lagrange multipliers technique. The mathematical model consists of a boundary value problem governed by the p-Laplace operator. Firstly, we deliver a mixed variational formulation. Secondly, we discuss the unique solvability of the mixed variational problem into an abstract functional framework, paying attention to the stability of the solution, too. Then, we apply the abstract results in order to study the unique weak solvability of the boundary value problem under consideration. The stability of the weak solution is also discussed.